LIFESI2O6 AND NAFESI2O6 AT LOW TEMPERATURES: AN INFRARED SPECTROSCOPIC STUDY - Zhang M.; Salje E.K.H.; Mookherjee M.; Redhammer G.J. (My University, 2002)
Synthetic aegirine LiFeSi2O6 and NaFeSi2O6 were characterized using infrared spectroscopy in the frequency range 50–2000 cm−1, and at temperatures between 20 and 300 K. For the C2/c phase of LiFeSi2O6, 25 of the 27 predicted infrared bands and 26 of 30 predicted Raman bands are recorded at room temperature. NaFeSi2O6 (with symmetry C2/c) shows 25 infrared and 26 Raman bands. On cooling, the C2/c–P21/c structural phase transition of LiFeSi2O6 is characterized by the appearance of 13 additional recorded peaks. This observation indicates the enlargement of the unit cell at the transition point. The appearance of an extra band near 688 cm−1 in the monoclinic P21/c phase, which is due to the Si–O–Si vibration in the Si2O6 chains, indicates that there are two non-equivalent Si sites with different Si–O bond lengths. Most significant spectral changes appear in the far-infrared region, where Li–O and Fe–O vibrations are mainly located. Infrared bands between 300 and 330 cm−1 show unusually dramatic changes at temperatures far below the transition. Compared with the infrared data of NaFeSi2O6 measured at low temperatures, the change in LiFeSi2O6 is interpreted as the consequence of mode crossing in the frequency region. A generalized Landau theory was used to analyze the order parameter of the C2/c–P21/c phase transition, and the results suggest that the transition is close to tricritical.
Keywords: LiFeSi2O6; NaFeSi2O6; Infrared spectroscopy; Low temperature; Phase transition